2018
DOI: 10.1080/10803548.2018.1485992
|View full text |Cite
|
Sign up to set email alerts
|

Design for occupational safety and health of workers in construction in developing countries: a study of architects in Nigeria

Abstract: The findings are thus symptomatic of the prevalence of influential DfS implementation barriers within the construction sector. Industry stakeholders should seek to raise the profile of DfS practice within the sector. Furthermore, similar empirical studies in the construction sector of other developing countries would be useful in shedding light on the status of DfS in these countries.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

8
54
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 42 publications
(77 citation statements)
references
References 25 publications
8
54
0
1
Order By: Relevance
“…Despite the socio-economic importance of the construction sector, the sector is infamous for being responsible for an alarming number of occupational fatalities, injuries and illnesses around the world (Atkinson and Westall, 2010;Votano and Sunindijo, 2014;Manu et al, 2019). A study by Martínez Aires et al (2016) showed that workers in the construction sector are more exposed than workers in other sectors to chemical and biological risks, as well as noise and temperature hazards.…”
Section: Status Of Construction Sector Occupational Safety and Health (Osh) In Palestinementioning
confidence: 99%
See 3 more Smart Citations
“…Despite the socio-economic importance of the construction sector, the sector is infamous for being responsible for an alarming number of occupational fatalities, injuries and illnesses around the world (Atkinson and Westall, 2010;Votano and Sunindijo, 2014;Manu et al, 2019). A study by Martínez Aires et al (2016) showed that workers in the construction sector are more exposed than workers in other sectors to chemical and biological risks, as well as noise and temperature hazards.…”
Section: Status Of Construction Sector Occupational Safety and Health (Osh) In Palestinementioning
confidence: 99%
“…This argument is in line with the findings by Ling et al (2009) that pressurising the workers to finish the job quickly increases the probability of accidents occurrence. In view of the expected increase in global construction output by 85% by 2030 (Global Construction Perspectives and Oxford Economics, 2015), Manu et al (2019) hinted that the existing poor construction OSH profile in developing countries might even deteriorate unless appropriate actions are implemented. Design for safety is one of such actions/mechanisms by which occupational accidents, injuries and illnesses can be mitigated in construction (Behm, 2005, Gibb et al, 2006.…”
Section: Status Of Construction Sector Occupational Safety and Health (Osh) In Palestinementioning
confidence: 99%
See 2 more Smart Citations
“…Consequently, construction workers have to change their working locations frequently. Researchers showed that workers in the construction industry normally suffer from high rates of mental health problems [10] and on-site accidents [11] but not all of them are offered sufficient health insurance [12]. Moreover, construction projects are becoming more complex and challenging [13].…”
Section: Introductionmentioning
confidence: 99%